Influence of Blocker Distance Variations in form of Triangle in Front of Cylinder toward Drag Coefficien - Gunawan Tista, Si Putu Gede (Jurnal Energi Dan Manufaktur, 2012)
One of the ways to reduce energy consumption on the air plane and the other bluff bodies are by decreasing the drag. Drag isclosely related to the flow separation. The earlier separation, then the drag will increase more. Based of the fact the effort todecrease drag is conducted by manipulating the field of fluid flow. Stream manipulation was be done by installing Triangleobstacle in front of cylinder. The purpose of this research is to analyze the effect of various distance triangle obstacle in front ofcylinder on drag. The present experiment was done by placing triangle rod in front of the cylinder. In the present research, theexperiment was conducted in the wind tunnel, which consisted of blower, pitot pipe, manometer, cylinder pipe, and triangle rod.The triangle was positioned at L/D = 1.19, L/D = 1.43, L/D = 1.67, L/D = 1.9, L/D = 2.14, L/D = 2.38, L/D = 2.62, and L/D =2.86 by upstream from the cylinder. The triangle was 8 mm uniform side. The Reynolds number based on the cylinder diameter (D= 42 mm) was Re = 1.81 x 104. The research results showed that the triangle rod could decrease the drag of cylinder. Coefficientdrag for cylinder without triangle rod was 0.1276 while the biggest decrease of coefficient of drag with triangle rod washappened at L/D = 1.43 which was 0.0188. It means that the drag of cylinder with triangle rod was 85.25% lower than thecylinder alone.
Keywords: Triangle obstacle, Obstacle distance, Sseparation, Drag reduction.